Online bike: Role of perceived technology, perceived risk, and institution-based trust on service usage via online trust - Lilik N. Yuliati; Hasdevi A. Dradjat; Megawati Simanjuntak (Cogent Business & Management, 2020)
This research aimed to analyze the effect of perceived technology, perceived risk, and institution-based trust on online trust and service usage of online bike-sharing services in Indonesia. As many as 200 respondents were chosen through systematical random sampling techniques. The data obtained were processed using descriptive method and structural equation modeling (SEM) through LISREL 8.7 software. The findings revealed that online trust were predicted by the perceived technology (path coefficient = 0.44; t-value = 11.27) and institution-based trust (path coefficient = 0.73; t-value = 15.47). However, the effect of perceived risk on online trust was not evident (t-value = 1.73). The service usage was determined by the perceived technology positively (path coefficient = 0.55; t-value = 11.25), perceived risk (path coefficient = −0.06; t-value = 3.56), and online trust (path coefficient = 0.05; t-value = 2.02). Also, perceived technology (path coefficient = 0.03; t-value = 2.05) and institution-based trust indirectly affected service usage via online trust (path coefficient = 0.04; t-value = 1.99). The Implications for experts and the governments as well as suggestions for future research are discussed.
Keywords: 650; online bike; perceived technology risk; service usage; trust